2004
DOI: 10.1111/j.1365-2929.2004.01872.x
|View full text |Cite
|
Sign up to set email alerts
|

Helping medical students identify their emotional intelligence

Abstract: ments in student satisfaction. Between 2001 and 2003, the level of student satisfaction increased by 16% for access to administration, by 20% for student participation on key committees, by 26% for administrative awareness of student concerns, by 35% for responsiveness of the administration to student concerns, and by 22% for career planning services. The initiative is now in its third year of implementation and new focus areas have been identified each year. The level of student involvement has been excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Females scored significantly higher on overall EI, empathy and the utilization of emotions subscales. A study from the Peninsula Medical School which focused on students' perceptions of the utility of EI, reported that the majority of the students liked to learn about the psychology of EI and valued identifying their emotional competencies and areas for development (Lewis et al 2004). Another study by Stratton et al (2005) found empathic concern to be a significant predictor of medical students' physical examination skills.…”
Section: Practice Pointsmentioning
confidence: 97%
“…Females scored significantly higher on overall EI, empathy and the utilization of emotions subscales. A study from the Peninsula Medical School which focused on students' perceptions of the utility of EI, reported that the majority of the students liked to learn about the psychology of EI and valued identifying their emotional competencies and areas for development (Lewis et al 2004). Another study by Stratton et al (2005) found empathic concern to be a significant predictor of medical students' physical examination skills.…”
Section: Practice Pointsmentioning
confidence: 97%
“…A recent review, containing some new data, from the Peninsula Medical School in UK and the University of Adelaide, has criticized the use of EI in a medical setting (Lewis et al 2005), based on questions concerning the construct validity and psychometric properties of EI measures. A further study from the Peninsula Medical School focused on students' views of the utility of this measurement (Lewis et al 2004), reported that the majority of the students welcomed the opportunity to learn about the psychology of EI, and also valued identifying (using the emotional competency inventory) their competencies and areas for development. A study from Kentucky (Stratton et al 2005) using the trait meta-mood scale and Davis' interpersonal reactivity index, found empathic concern to be a significant predictor of students' physical examination skills.…”
Section: Introductionmentioning
confidence: 97%
“…One such factor, emotional intelligence (EI), is increasingly made reference to in medicine, nursing and other healthcare disciplines where it is suggested it is important for professional mental health as well as effective practice [2,14-16]. The concept of EI was introduced over a decade ago by Salovey and Mayer [17] and is described as 'a type of social intelligence that involves the ability to monitor one's own and other's emotions, to discriminate among them, and to use this information to guide one's thinking and actions'.…”
Section: Introductionmentioning
confidence: 99%